Libre comercio e integración comercial en la Alianza del Pacífico y la Comunidad Andina - Saldaña Pacheco, Raphael Ángel (2018)
Objective: The research established the effect of the international trade freedom index on the level of trade integration in some countries that currently make up the Pacific Alliance (AP) and the Andean Community (CAN) during the period 1970-2015. Method: The study approach is quantitative because statistical procedures were used, in strict correlation coefficient and regression analysis. Results: One of the main results is that there is a positive and statistically significant relationship between the freedom of international trade index and the degree of commercial integration among the member countries of the PA and the CAN. This relation is differentiated among these countries and within each group. However, at the aggregate level, the effect of the index of freedom of international trade on the degree of commercial integration is greater in the countries of the PA than in those of the CAN. Conclusions: It was concluded that the freedom of international trade influenced the level of commercial integration in the member countries of the PA and the CAN. However, this effect is not sufficient to determine the degree of commercial integration in the PA and CAN.